MODEL PENYEBARAN HIV DIANTARA PENGGUNA NARKOBA DENGANJARUM SUNTIK - Utaminingsih
This final project will analyze models for the spread of HIV/AIDS amongst a population of injecting drug users. Start off with a brief literature review, followed up by a detailed description of Kaplan’s model and another realistic extension of Kaplan’s model. Then perform an equilibrium and stability analysis on these models. There is a critical threshold parameter R0 which determines the behavior of the models. Basic Reproduction Ratio (R0) is expected values of secondary infections caused by a single infected individual in an entirely susceptible population. Basic Reproduction Ratio (R0) indicate whether the endemic disease appear in entirely population or not. If R0 >1, it means that the endemic disease occurs in population. In another way if R0 <1, it means that the endemic disease will not occurs. These results are confirmed and explored further by simulation.